Software-Defined Radio Testbed for 6G Research - Ahmad, Sajeel; Collard, Niclas Christopher; Martinsson, Martin; Mörck, Gabriel; Rahimi, Sammy (My University, 2026)
The increasing demand for wireless communication and the limitations of current cellular networks motivate research into new cellular network architectures. Traditionally, the philosophy in cellular networks has been to have one base station per geographical area, and that a cellular user is only connected to one base station at a time. This has limitations with regard to uneven coverage and poor cellular quality far from base stations. Distributed multiple-input multiple-output (D-MIMO) systems aim to resolve those limitations, providing users with improved cellular network performance. Chalmers University of Technology has a D-MIMO testbed that is used in research. Although the testbed fulfills its intended purpose, its current setup is based on costly laboratory equipment, which limits experimental flexibility and restricts scalability. Therefore, this thesis aims to implement a more flexible and cost-effective method to emulate user equipment in the current testbed. The project first focused on designing and validating a point-to-point communication link between two software-defined radios, evaluating several key aspects of the radios, including bandwidth limitations, maximum achievable throughput, and limitations related to signal duration and onboard memory. The results show that the system can operate with a maximum bandwidth of 49.51 MHz and a maximum throughput of 54.25 Mbit/s. The developed communication system enables reliable data transmission and reception, using preambles to detect and correct transmission errors and verify the accuracy of the transmitted data. It operates without external reference signals and compensates for carrier frequency offsets. Bit error rate (BER) and error vector magnitude (EVM) were used to evaluate the system. In indoor conditions, a BER of 0 and an EVM of 6.25% were achieved, allowing it to transmit data reliably between two radios. The system was also successfully integrated into the D-MIMO testbed, where it was subjected to strict synchronization constraints. The transmitted signal was successfully received by all six remote radio heads and combined using maximum ratio combining, achieving a BER of 0 and an EVM of 4.64%.
Keywords: 6G testbed, USRP, software-defined radio, distributed MIMO.